Examining the Relationship between Organizational Culture Alignment and Employee Creativity in Knowledge Process Outsourcing - Ramirez, Kirk Lile; Almaden, Antoniette; Delantar, Alexander Franco (JPAIR Multidisciplinary Research, 2025)
Organizational culture plays a crucial role in fostering creativity and innovation in the workplace. This quantitative correlational study examined the relationship between organizational culture alignment and employees’ perceived creativity among 42 Knowledge Process Outsourcing employees at a KPO company at Cebu I.T. Park, Philippines. Grounded in the componential theory of creativity, the study explored how cultural alignment influences intrinsic motivation, cognitive processes, and creative output. A 6-Likert scale survey was used to assess employees’ perceptions of cultural alignment and their self-reported creativity. Results revealed a weak but statistically significant positive correlation (r = 0.33, p = 0.031), suggesting that greater alignment with the company’s advocated culture is associated with a slight increase in employees’ creative engagement. While findings indicate a potential connection between culture and creativity, the weak correlation suggests that other factors may also contribute to workplace creativity. Future research is recommended to explore additional variables influencing innovation and problem-solving in Knowledge Process Outsourcing environments.